2011
DOI: 10.1155/2011/463184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Nevogenesis

Abstract: Despite recent advances, the biology underlying nevogenesis remains unclear. Activating mutations in NRAS, HRAS, BRAF, and GNAQ have been identified in benign nevi. Their presence roughly correlates with congenital, Spitz, acquired, and blue nevi, respectively. These mutations are likely to play a critical role in driving nevogenesis. While each mutation is able to activate the MAP kinase pathway, they also interact with a host of different proteins in other pathways. The different melanocytic developmental pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 55 publications
3
52
0
1
Order By: Relevance
“…An extraordinarily high NRAS mutation frequency seems to be characteristic of medium-sized (≥1.5 cm) and large-giant congenital nevi whereas common acquired nevi and Spitz nevi have rare NRAS mutations (4.6% and 4%, respectively) [39].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 98%
See 1 more Smart Citation
“…An extraordinarily high NRAS mutation frequency seems to be characteristic of medium-sized (≥1.5 cm) and large-giant congenital nevi whereas common acquired nevi and Spitz nevi have rare NRAS mutations (4.6% and 4%, respectively) [39].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 98%
“…The frequency of NRAS mutations in medium-sized congenital nevi is 64-70% [39][40][41] and raises to 94.7% in large-giant congenital nevi where it has been recently recognized as the sole recurrent somatic mutation [42]. It has been suggested that NRAS mutations exert stronger growth signals, resulting in the formation of larger nevi than those linked to BRAF mutations [43].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…66,[97][98][99][100] In particular, mutations in HRAS have been frequently detected in Spitz nevi. 101 Congenital nevi often harbor mutations in NRAS gene, 102,103 whereas acquired nevi are composed of melanocytes carrying BRAF mutations. 99 The same mutations in these genes were found in malignant melanomas albeit surprisingly at frequencies lower than that in benign nevi, 99,104,105 suggesting that malignant melanomas, which are frequently derived from nevi, have developed a mechanism(s) for suppressing OIS.…”
Section: Different Types Of Oismentioning
confidence: 99%
“…In acquired nevi (mainly epidermal and junctional) BRAF and NRAS mutations occur in almost 79% (Pollock 2003, Uribe 2006, Venesio 2008and Ross 2011 and 4.6% (Saldanha 2004, Gill 2004, Poynter 2006and Venesio 2008 of cases of acquired nevi respectively. 65% of dysplastic/atypical nevi carry BRAF mutations (Pollock 2003 andUribe 2006).…”
Section: Acquired Nevimentioning
confidence: 99%
“…Although the nature of this process is not well understood. Activation of certain molecular pathways is crucial to drive nevogenesis (Ross 2011). The life cycle of benign melanocytic lesions can consist of four stages: initiation, promotion, senescence, and occasionally involution.…”
Section: Nevogenesismentioning
confidence: 99%